Analysis of financial performance of Sector 9 Companies: Trade, Services, and Investment listed on the LQ 45 Index of the Indonesia Stock Exchange in 2022 - Yosia, Yosia; Sasono, Agus Dwi; Indah, Sri; Indrihastuti, Popy (Journal of Economics and Business Letters, 2024)
This study aims to determine and analyze the financial performance of Sector 9 companies: Trade, Services, and Investment, listed on the Indonesia Stock Exchange (IDX) in 2022. This research is quantitative descriptive, focusing on the calculation of data in the form of annual financial reports of manufacturing companies listed on the IDX. The data used is secondary, consisting of documents obtained from the official IDX website (www.idx.co.id). The study results indicate the following: 1) Based on the current ratio or liquidity, the financial performance of the IDX- listed companies in the sample shows good and significant coefficient values; 2) Based on the debt to equity ratio or solvency, the financial performance of the IDX- listed companies in the sample also indicates good and significant coefficient values; 3) Based on profitability, the financial performance of Sector 9 companies: Trade, Services, and Investment listed on the IDX in the sample show very good coefficient values.